Hukuman Kebiri Kimia Bagi Pelaku Kejahatan Seksual Terhadap Anak Berdasarkan Ketentuan Undang-Undang Nomor 17 Tahun 2016 - Jamaluddin Jamaluddin; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (USU LAW JOURNAL, 2019)
Abstract. Sexual violence in children is a form of child abuse in which adults of teenagers abused a child for sexual stimulations. Almost all cases reveal that the perpetrator of sexual violence is the victim’s close relatives, such as biological parents, step parents, uncles, teachers, and neighbors. Based on the above problem, the problem of this thesis is as follows. How is the provision of criminal sanctions against the perpetrators of moral offenses according to Law No 17/2016. This case has encouraged the establishment of provisions based in the Law No. 17/2016. The regulations on castration penalty are stipulated in Article 81 paragraph (7) as referred to in paragraphs (4) and (5) stating that the perpetrator is sentenced with castration by chemicals accompanied with rehabilitations. Chemical castration is the injection of anti testosterone substance into males to reduce testosterone hormone, most of which is produced by lydig in testis. The provisions of a witness of chemical castration penalty are stipulated in the Law No. 1/2016 on the Second Amendment to the Law No. 23/2002 on Child Protection becoming the Law No. 35/2014. Article 81 paragraphs (1) until (8), 82, and 81A of the Law has an additional penalty for the perpetrator, one of which is the castration penalty to the perpetrator of sexual violence to undergo children.   Keywords : chemical castration penalty, sexual violence in children